2017
DOI: 10.1111/gcb.14006
|View full text |Cite
|
Sign up to set email alerts
|

Climate change leads to differential shifts in the timing of annual cycle stages in a migratory bird

Abstract: Shifts in reproductive phenology due to climate change have been well documented in many species but how, within the same species, other annual cycle stages (e.g. moult, migration) shift relative to the timing of breeding has rarely been studied.When stages shift at different rates, the interval between stages may change resulting in overlaps, and as each stage is energetically demanding, these overlaps may have negative fitness consequences. We used long-term data of a population of European pied flycatchers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(106 citation statements)
references
References 86 publications
(142 reference statements)
4
94
0
1
Order By: Relevance
“…The recent increase in temperature caused by climate change causes changes in the timing of annual cycle stages but not at the same rates (Both & Visser, ; Crozier et al., ; Ozgul et al., ; Moyes et al., ; Tomotani, van der Jeugd, et al (Submitted)). This means that this already short interval between breeding and moult may be either further reduced depending on how fast breeding and moult shift Tomotani, van der Jeugd, et al (Submitted). Earlier breeding, on the other hand may also allow a longer duration of moult if departure does not change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent increase in temperature caused by climate change causes changes in the timing of annual cycle stages but not at the same rates (Both & Visser, ; Crozier et al., ; Ozgul et al., ; Moyes et al., ; Tomotani, van der Jeugd, et al (Submitted)). This means that this already short interval between breeding and moult may be either further reduced depending on how fast breeding and moult shift Tomotani, van der Jeugd, et al (Submitted). Earlier breeding, on the other hand may also allow a longer duration of moult if departure does not change.…”
Section: Discussionmentioning
confidence: 99%
“…We used this information to calculate the proportion of (locally) surviving birds from each treatment and, in the case of the females, we also obtained the next year laying dates and clutch sizes. The male comparison, however, need to be treated with care, because mostly males from the control group were deployed with geolocators after the experiment ended (24 controls and 5 plucked, for purposes not related to the present experiment, Tomotani, van der Jeugd, et al ()), which could impose an additional constraint to the survival probability for this group (Bowlin et al., ). The male survival comparison is still relevant since previous geolocator studies with pied flycatcher reported low impact on return rates of tagged birds in comparison to controls (Ouwehand & Both, ).…”
Section: Methodsmentioning
confidence: 99%
“…The effects of climate change on moult extent, duration and timing are largely unknown. Surprisingly, most studies that investigate the effects of climate change on avian life‐history traits do not mention moult (Stenseth & Mysterud, ; Winkler, Dunn & McCulloch, ; Crick, ; Both & Visser, ; but see Hedenström et al, ; Tomotani et al, ), despite its importance for understanding bird ecology and evolution, particularly with regard to life‐history transitions under current and expected global climate changes.…”
Section: Directions For Future Studymentioning
confidence: 99%
“…Migratory individuals depend on a wide range of temporally and spatially distributed habitats and resources across the annual cycle, which is thought to expose migrants—especially long‐distance migrants—to increased potential risks (Both et al, ; Gilroy, Gill, Butchart, Jones, & Franco, ; Robinson et al, ; Wilcove & Wikelski, ). Rising temperatures have been linked to poleward range shifts in migratory species (Breed, Stichter, & Crone, ; La Sorte & Thompson, ), shorter migration distances (Heath, Steenhof, & Foster, ; Visser, Perdeck, Balen, & Both, ), earlier arrival times (Jonzén et al, ; Usui, Butchart, & Phillimore, ) and earlier breeding times (Both et al, ; Tomotani et al, ). Furthermore, the capacity of migratory species to adapt to climate change is not universal (Fraser et al, ; Robinson et al, ), and inability to do so has been linked to population declines (Møller, Rubolini, & Lehikoinen, ).…”
Section: Introductionmentioning
confidence: 99%